2015
DOI: 10.1159/000439573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Neoadjuvant Combined Androgen Blockade for More Than Six Months in Patients with Localized Prostate Cancer Treated with Prostate Brachytherapy

Abstract: Introduction: The aim of this study is to clarify the clinical significance of neoadjuvant combined androgen blockade (CAB) for ≥6 months in patients with localized prostate cancer. Patients and Methods: A total of 431 patients with localized prostate cancer who underwent prostate brachytherapy (BT) with or without neoadjuvant CAB for ≥6 months with mean follow-up time of 64.6 months (range 24-108 months) were evaluated retrospectively. Of those 431, 232 patients received BT in combination with neoadjuvant CAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…Most of patients in these studies received short term ADT in order to downsize the prostate prior to brachytherapy. ADT consistently showed improved in bPFS in patients with lower BED/D90 (26,81,98,106), unfavourable IR (multiple risk factors) and majority of HR patients (55,56,88,90,9395)(97). …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most of patients in these studies received short term ADT in order to downsize the prostate prior to brachytherapy. ADT consistently showed improved in bPFS in patients with lower BED/D90 (26,81,98,106), unfavourable IR (multiple risk factors) and majority of HR patients (55,56,88,90,9395)(97). …”
Section: Discussionmentioning
confidence: 94%
“…Others reported that high quality implants may derive less benefit from supplemental EBRT (123) or ADT (26,81,98,106,123). The impact of ADT on OS has not been studied well, as only 19 studies (36%) reported association of ADT and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show favorable short-term results following LDR-BT for localized prostate cancer, in part because LDR-BT is primarily administered for low-and intermediate-risk cases (8,10). Our previous studies have also shown excellent short-term anticancer effects of LDR-BT in cases with lowand intermediate-risk of treatment failure (15). However, there are limited reports on the long-term results of LDR-BT in patients followed-up over 10 years after treatment (16).…”
Section: Discussionmentioning
confidence: 82%
“…Regarding adjuvant antiandrogen, a randomized trial found that its use improved neither PFS nor OS in men with localized PCa after RP [139]. The combination of neoadjuvant ADT and RT can lead to significant survival benefits in men with intermediate-risk PCa compared with RT alone [133,[140][141][142][143]; however, the optimal timing and duration of neoadjuvant ADT remain ill-defined. In the RTOG 9408 trial [133], the use of ADT for 4 months (starting 2 months before RT) was effective to improve disease-specific survival and OS among patients with intermediate-risk PCa.…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%
“…The 4-month ADT schedule was further supported by the RTOG 9910 trial [141], which found that extending the ADT duration to 7 months before RT did not improve survival outcomes. Yet, a retrospective study conducted in Japan showed that neoadjuvant ADT lasting for ≥6 months improved biochemical recurrence-free survival in patients with intermediate-risk PCa [143]; therefore, neoadjuvant ADT for 4-6 months can be given before the initiation of RT for intermediate-risk PCa. Statement 6: 'When RT is planned for patients with highrisk PCa, neoadjuvant (for 4-6 months) and adjuvant ADT (for 2-3 years) are recommended.…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%